Merger masters : tales of arbitrage - Welling, Kate; Gabelli, Mario (Columbia University Press, 2018)
"Merger Masters presents revealing profiles of monumentally successful merger investors based on exclusive interviews with some of the greatest minds to practice the art of arbitrage. Michael Price, John Paulson, Paul Singer, and others offer practical perspectives on how their backgrounds in the risk-conscious world of merger arbitrage helped them make their biggest deals. They share their insights on the discipline that underlies their fortunes, whether they practice the 'plain vanilla' strategy of announced deals, the aggressive strategy of activist investment, or any strategy in between on the risk spectrum. Merger Masters delves into the human side of risk arbitrage, exploring how top practitioners deal with the behavioral aspects of generating consistent profits from risk arbitrage. The book also includes perspectives from the other side of the mergers and acquisitions divide in the form of interviews with a trio of iconic CEOs: Bill Stiritz, Peter McCausland, and Paul Montrone. All three took advantage of M & A opportunities to help build long-term returns but often found themselves at odds with the short-term focus of Wall Street and merger investors. Told in lively, accessible prose, with bonus facts and figures for transaction junkies, Merger Masters is an incomparable set of stories with plenty of unfiltered lessons from the best managers of our time."--